Polinização, sistema reprodutivo e abelhas visitantes de duas espécies simpátricas de Byrsonima (Malpighiaceae) em área de cerrado no Maranhão, Brasil - MENDES, Fernanda Nogueira (2007)
(Pollination and Reproduction System of Byrsonima umbellata Mart. (Malpighiaceae) in Cerrado at Maranhão, Brazil). The reproductive biology of Byrsonima umbellata was studied in a Cerrado area close to Bom Jesus (03°12'28 '' S, 43°24'12 '' W) far from 46 km of the municipal district of Urbano Santos, northeast of Maranhão, Brazil, from Mar to Oct/2005 and Mar to Oct/2006. Flowering phenology, morphology and floral biology were studied and bees visitors were observed. The breeding system was verified through experimental pollinations in the field. Byrsonima umbellata is a specie with hermaphrodite flowers, of diurnal anthesis and high pollen viability. The flowering pattern is annual, extensive and irregular, having production of buds and flowers more or less constant along the months. The controlled pollinations showed that the species is partially self-incompatible. Forty two species of bee visitors were observed. The tribe Meliponini presented larger abundance, while the wealth was larger in the Centridini tribe.